Músicas populares y bicentenarios en el espacio urbano andino. El caso de la “Guerra del Charango - Leonardo García (Nuevo mundo - Mundos Nuevos, 2011)
The following paper synthesizes the subject “Popular music and Bicentenaries. Creation, music practice and social representations in the urban Andean area” approaching the development of contemporary “Andean music” and its relationship with Latin American Bicentenaries. The paper analyses the impact of music on the valorization of ethnicity, localness and community values, as vectors of social integration to new postmodern nationalisms. The subject concerns the evolution of the Andean lute charango, a musical instrument that has expanded towards a Global dimension since these last two decades.